Precarization or Empowerment? Reflections on Recent Labor Unrest in China - Lee, Ching Kwan (The Journal of Asian studies, 2016)
Labor scholars have highlighted the predicament of “precarization” besetting the working class everywhere in the twenty-first century. Beneath the “proletariat” now stands the “precariat,” for whom exploitation seems like a privilege compared to constant exclusion from the labor market. Amidst worldwide employment informalization and decimation of workers’ collective capacity, media reports and academic writings on Chinese workers in the past several years have singularly sustained a curious discourse of worker empowerment. Strikes in some foreign-invested factories have inspired claims of rising working-class power. Finding little empirical support for the empowerment thesis, this article spotlights the Chinese peculiarity of the global phenomenon of precarization and the dynamics of recent strikes, suggesting the need for Chinese labor studies to rebalance its prevailing voluntarism and optimism with more attention to institutional and political-economic conditions.